Intraspecific diversity matters in bryophyte conservation – internal transcribed spacer and rpl16 G2 intron variation in some European mosses. (2nd July 2016) - Hedenäs, Lars
Abstract : Intraspecific diversity and molecular relations among regional populations were studied for 16 moss species in three European regions, Central Europe, Southern Scandinavia, and Northern Scandinavia, based on internal transcribed spacer and rpl 16 G2 intron. The range of nuclear diversity values found is mainly similar to that of other organisms, and to that found in bryophytes from other regions, but higher diversity was found in Isothecium alopecuroides (Dubois) Isov. No correlations were found between diversity values or number of haplotypes unique to a region and morphological diversity, geographical distribution range, or regional frequency, possibly since this study did not include sufficiently rare species to reflect the factors affecting such species. Finally, no general differences in diversity levels were found among the three studied regions. When haplotype composition is considered, differences were found among the regions for some species, but again no general inter-regional pattern of intraspecific relationships exists. While it is clear that intraspecific variation is crucial to consider in biodiversity conservation contexts since a high proportion of the total diversity is found below the species level, it is also evident that it is necessary to investigate each individual species rather than to rely on what has been found for other taxa.